Blood eosinophilia, use of inhaled corticosteroids, and risk of COPD exacerbations and mortality - Oshagbemi, Olorunfemi A. (Pharmacoepidemiol Drug Saf, 2018)
PURPOSE: It remains unclear whether eosinophilia is useful for in guiding inhaled corticosteroid (ICS) therapy in chronic obstructive pulmonary disease (COPD) patients. The goal of this study is to evaluate the risk of acute exacerbations, COPD‐related hospitalisations/accident and emergency visits, and all‐cause mortality with various levels of eosinophil counts among COPD patients using ICS. METHODS: A cohort study was conducted using the UK Clinical Practice Research Datalink. Patients were aged 40+ and had COPD (n = 32 693). Current users of ICS were stratified by relative and absolute eosinophil counts to determine the risk of outcomes with blood eosiniphilia using Cox regression analysis. RESULTS: Among COPD patients, current use of ICS was not associated with a reduced risk of acute COPD exacerbations, COPD‐related hospitalisations/accident and emergency visits, and all‐cause mortality. Stratification of ICS use by absolute or relative eosinophil counts did not result in significant differences in risk of COPD exacerbations or hospitalisations/accident and emergency visits. However, all‐cause mortality was reduced by 12% to 24% among patients with eosinophilia. CONCLUSIONS: COPD‐related acute exacerbations or hospitalisations/accident and emergency visits were not reduced with eosinophilia among users of ICS with COPD. However, all‐cause mortality was reduced by 12% to 24%. These findings are potentially important and require further evaluation in prospective studies.